Identifying Emotional Expressions: Children’s Reasoning About Pretend Emotions of Sadness and Anger - Serrat, Elisabet; Amadó, Anna; Rostan, Carles; Caparrós, Beatriz; Sidera, Francesc (Frontiers in Psychology, 2020)
This study aims to further understanding of children’s capacity to identify and reason about pretend emotions by analyzing which sources of information they take into account when interpreting emotions simulated in pretend play contexts. A total of 79 children aged 3 to 8 participated in the final sample of the study. They were divided into the young group (ages 3 to 5) and the old group (6 to 8). The children were administered a facial emotion recognition task, a Pretend Emotions task, and a non-verbal cognitive ability test. In the central task, the Pretend Emotions task, the children were asked whether the protagonist of silent videos, who were displaying pretend emotions (pretend anger and pretend sadness), was displaying a real or a pretend emotion, and to justify their answer. The results show significant differences in the children’s capacity to identify and justify pretend emotions according to age and type of emotion. The data suggest that young children recognize pretend sadness, but have more difficulty detecting pretend anger. In addition, children seem to find facial information more useful for the detection of pretend sadness than pretend anger, and they more often interpret the emotional expression of the characters in terms of pretend play. The present research presents new data about the recognition of negative emotional expressions of sadness and anger and the type of information children take into account to justify their interpretation of pretend emotions, which consists not only of emotional expression but also contextual information.